Forecasting Methods in Science Education: A Bibliometric Analysis Using the Scopus Database - Suhendar, Suhendar; Widodo, Ari; Solihat, Rini; Riandi, Riandi (KnE Social Sciences, 2024)
This study utilizes a detailed bibliometric analysis to thoroughly explore the literature surrounding forecasting methods and models in science education. It highlights significant trends, applications, and impacts of these methodologies. Leveraging data from the Scopus database pinpoints essential themes and notable gaps within the current body of work. The research underscores the importance of integrating forecasting techniques across various scientific disciplines and applying these techniques to address real-world challenges in education. This comprehensive analysis is intended to contribute richly to academic dialogue and guide the development of future educational strategies and policies. By identifying and discussing these key elements, the study aims to enhance understanding and implementing forecasting methods in academic settings, ultimately influencing both practice and theory in science education. Keywords: forecasting methods, science education, bibliometric